Infant feeding and subsequent risk of atopic eczema. Issue 8 (August 1985) - Moore, W J; Midwinter, R E; Morris, A F; Colley, J R; Soothill, J F
Abstract : An attempted controlled trial of exclusively breast fed neonates with atopic parents, to assess the effectiveness of breast feeding in preventing atopic allergy, was not successfully achieved. Analysis of the data as an observational study, however, provided evidence that breast feeding offers some protection against eczema in genetically vulnerable infants. Feeds of soya preparations were associated with eczema as often as cows' milk based feeds.